Food and Power in Early Medieval England: Rethinking Feorm. (20th December 2020) - Lambert, Tom; Leggett, Sam
ABSTRACT: It has long been accepted that royal households in the pre-Viking period subsisted on annual renders of food, sometimes termed feorm, from the free peasantry. This model of royal support is historiographically fundamental, in the sense that it is built into the foundations of much current thinking not just on the economics of kingship, but on its origins, and on the process of 'manorialization'. This article argues that the texts which are conventionally read as references to these general-purpose food supplies are in fact concerned with feasts. This is apparent when we scrutinize both the content of food lists – which are so dominated by animal protein as to be inconsistent with the stable isotope evidence for elite diet examined in our companion article – and the contexts of documentary references to feorm and (in Latin) pastus. The article concludes with a review of the potentially far-reaching implications of this finding.